OFR-25(2)-73 Respirable Dust Control Manual For Underground Coal Mines - 1.0 Introduction - Jerome Apt (The National Institute for Occupational Safety and Health (NIOSH), 1972)
This manual has been prepared fur the help and guidance of underground coal mine operators. It details both common and unique engineering methods by which the respirable dust, which is generated in coal mines, can be controlled. This document was compiled by Apt, Bramer, Conrad and Associates, Inc. under contract number H0111464, issued by the U. S. Bureau of Mines and forms Volume II of the final report. This contract was authorized by and executed pursuant to the Federal Coal Mine Health and Safety. Act of 1969 (P. I. 91-173; 83 Stat. 742).